Chemical Pulps for Writing and Printing Papers from Ailanthus excelsa Roxb - Guha, S. R. D.; Pant, P. C. (Indian Forester, 1961)
Laboratory experiments on the production of chemical pulps from Ailanthus excelsa suitable for writing and printing papers by sulphate process are described. The average fibre length of the pulp was 1.33 mm. and the average fibre diameter was 0.035 mm. Easy bleaching pulps in good yields with satisfactory strength properties could be prepared under suitable conditions.